The Therapeutic Benefits of Reusi Dat Ton: Assessing Stress Reduction, Resilience, and Mobility Improvements Using a Stress Test, Cardiac Health Monitor, and Inertial Measurement Unit Technology: Assessing Reusi Dat Ton for Stress and Mobility - Nanbancha, Ampika; Tharawadeepimuk, Kittichai; Limroongreungratt, Weerawat; Leelawapa, Nuchanath; Wongsawat, Yodchanan; Sroykham, Watchara (Vajira Medical Journal : Journal of Urban Medicine, 2025)
OBJECTIVE: Reusi Dat Ton, also known as Thai Yoga, is a traditional therapeutic exercise recognized for its potential in managing health issues such as office syndrome and stress. This study aimed to evaluate the effects of Reusi Dat Ton on neck and shoulder range of motion (ROM) using inertial measurement unit (IMU) technology, and on stress levels assessed via heart rate variability and the Suanprung Stress Test-20 (SPST-20). METHODS: Forty-five participants (21 males, 24 females) with a mean age of 35.73 years and a mean body mass index of 23.49 were evaluated pre and post intervention in a 20-minute five specific Reusi Dat Ton therapeutic exercises. Stress levels were assessed using the SPST-20 and a cardiac health monitor, while ROM was measured using the Ultium Motion system with IMU technology. RESULTS: The Reusi Dat Ton intervention led to significant reductions in SPST-20 scores (p < 0.001) and heart rate (p < 0.001), along with significant improvements in stress resilience (p < 0.01) and right shoulder flexion (p < 0.05). CONCLUSION: Reusi Dat Ton effectively reduced stress levels, enhanced stress resilience, and improved right shoulder mobility. These findings support its use as a therapeutic exercise for individuals with office syndrome and related conditions.